Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.31219/osf.io/cm9tq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specificity of Brain Volume Alterations in Children with Various Parental Histories of Psychopathology

Abstract: Background: Multiple forms of parental psychopathology have been associated with differences in child subcortical brain volume. Much of this work has relied on studies of individual forms of parental psychopathology without considering the role of comorbid disorders. Here, we examine the specificity of relationships between multiple forms of parental psychopathology and alterations in child subcortical brain structure. Method: We examined 6581 children from the ABCD study with no history of mental disorders. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…ABCD Study findings have revealed smaller volume in the right putamen (Pagliaccio et al, 2020), left hippocampus (Chen et al, 2010), and bilateral hippocampi (Rao et al, 2010), aligning with our results. However, studies using other datasets have found that parental history of depression is associated with larger volume in the bilateral amygdala (Lupien et al, 2011), and others have reported no effects (Mattoni et al, 2023). ELA dimensions that indicated the potential presence of household hostility including family aggression (e.g., throwing things, hitting) (F8) revealed a positive main effect for fMRI BAG, but no effects for family arguments (e.g., expressing anger, fighting, raising voices) (F7), with the latter finding going against our hypothesis.…”
Section: Links To Accelerated Brain Maturationmentioning
confidence: 94%
“…ABCD Study findings have revealed smaller volume in the right putamen (Pagliaccio et al, 2020), left hippocampus (Chen et al, 2010), and bilateral hippocampi (Rao et al, 2010), aligning with our results. However, studies using other datasets have found that parental history of depression is associated with larger volume in the bilateral amygdala (Lupien et al, 2011), and others have reported no effects (Mattoni et al, 2023). ELA dimensions that indicated the potential presence of household hostility including family aggression (e.g., throwing things, hitting) (F8) revealed a positive main effect for fMRI BAG, but no effects for family arguments (e.g., expressing anger, fighting, raising voices) (F7), with the latter finding going against our hypothesis.…”
Section: Links To Accelerated Brain Maturationmentioning
confidence: 94%